Kepuasan Kerja Di Kalangan Atendan Kesihatan Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan - Ismail, Ibrahim (2002)

(untitled)
The concept of job satisfaction had been formed since 70 years ago. Driven by the goals to increase productivity and organization's profit, job satisfaction had been extensively studied especially in the field of management and psychology. Study done in this thesis are based on 2- Factor Theory by Frederick Herzberg with the objectives to identify (a) level of job satisfaction amongst Health Attendant in the Hospital Universiti Sains Malaysia (HUSM) in general (b) whether there are differences in job satisfaction amongst Health Attendant based on demographic atttributes of sex, level of education and period of service (c) whether there are relationship and influence of motivator factors and hygiene factors with job satisfaction amongst Health Attendant in HUSM (d) whether motivator factors and hygiene factors could significantly explain the variance in job satisfaction and (e) the most suitable element in predicting job satisfaction. Questionnaire divided with 3 sections are the instrument used in this study. Section A of the questionnaire consist of items related with demographic attributes. Section B are based on questionnaire developed by Brayfield - Rothe (1951) which consist of items to measure job satisfaction in general while Section C composed of questionnaire to measure 14 elements of job satisfaction adopted from Faculty Opinion Survey by Seegmiller (1977) and subsequently modified by Abu Bakar Hashim (1 985). 189 Health Attendant were the sample of this study. Data were analysed by SPSS Version 10.0 and descriptive statistics, Pearson Product-Moment correlation analysis, t-test, ANOVA test, multiple regression and Stepwise regression analysis were used as statistical tools. Findings of the study indicate that (a) 14.8% of Health Attendant has high job satisfaction, 84.7% in medium job satisfaction and 0.5% with low job satisfaction (b) there are significant differences in job satisfaction based on demographic attribute along level of education. There are no significant differences in job satisfaction along sex and period of service (c) there are significant relationship between job satisfaction with motivator factors but insignificant with hygiene factors. In term of influence, both motivator and hygiene factors has influencial impact on job satisfaction (d) both motivator and hygiene factors could explain the variance in job satisfaction (e) element of recognition appears as the best predictor for job satisfaction (f) two elements of motivator factors i.e recognition and job itself and one element under hygiene factors i.e personal life constitute 3 best elements in explaining variance in job satisfaction.